Kedudukan Dan Perlindungan Hukum Terhadap Whistleblower Dalam Mengungkap Tindak Pidana Korupsi Pengadaan Barang Dan Jasa Pemerintah - Intan Rosyidi; Rahman Amin (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2024)
Whistleblowers are parties who report and provide information to law enforcers about criminal acts of corruption that occur, but in fact, there are still cases where Whistleblowers do not receive protection in exposing criminal acts of corruption in the procurement of government goods and services. This research aims to find out what the position of Whistleblowers is in uncovering cases of criminal acts of corruption in the procurement of government goods and services, and how Whistleblowers are protected in uncovering cases of criminal acts of corruption in the procurement of government goods and services. The research method used is normative juridical with a statutory approach and a case approach. The research results show that the position of a Whistleblower is a fact-telling witness who provides information for the purposes of investigation, prosecution and trial regarding criminal acts of corruption in the procurement of government goods and services that occur as regulated in Law Number 31 of 2014 concerning Protection of Witnesses and Victims. Legal protection for Whistleblowers in cases of criminal acts of corruption in the procurement of government goods and services, although it has been regulated in Law Number 31 of 2014 concerning Protection of Witnesses and Victims, where implementation is carried out by LPSK and other law enforcement agencies, there are still several cases where Whistleblowers can be found. receive physical and psychological threats, as well as being criminally reported so that regulations regarding the protection of Whistleblowers need to be strengthened to provide maximum legal protection.